Management of bilioenteric anastomosis leakage after major liver resection - Abbasi Dezfouli, Sepehr; Heidenreich, Elmira; Shahrbaf, Mohammadamin; Khajeh, Elias; Chang, De-Hua; Klauß, Miriam; Mieth, Markus; Loos, Martin; Büchler, Markus W.; Mehrabi, Arianeb (BJS open, 2025)
Background Post-hepatectomy bile leakage is a challenging issue that can lead to morbidities and mortality after liver resection. This leakage can occur either from a bilioenteric anastomosis (BEA) or from the transected surface of the liver. This study investigated the incidence, risk factors, and effective management of BEA leakage after major liver resection. Methods Bile leakage was diagnosed through drain fluid analysis based on the International Study Group of Liver Surgery definition. Leakage from a BEA was confirmed via fluoroscopy during percutaneous interventions or reoperation. Perioperative data and data on the management of patients with BEA leakage were collected and analysed. Bivariate analysis used Mann-Whitney U and chi 2 tests, and binary logistic regression identified risk factors for BEA leakage, with variables having P < 0.200 included in multivariable analysis. Results Of 2936 patients undergoing hepatectomy between 2008 and 2023, 229 underwent liver resection with BEA. Leakage from the BEA was identified in 44 patients (19.2%). These patients had a higher rate of post-hepatectomy haemorrhage (P = 0.005), major complications (P = 0.001), BEA stenosis (P = 0.006), and mortality (P = 0.043). The success rate of the management of BEA leakage was 70% for reoperation and 58% for percutaneous transhepatic cholangiography and drainage (PTCD). Conclusion BEA leakage after major liver resection is a severe complication associated with higher morbidity and mortality rates. Surgical treatment appeared to be more successful than PTCD in the early postoperative phase. PTCD proved to be a valuable additional therapy option following reoperation. These conclusions should be taken with caution and need to be confirmed through further prospective studies.